2019
DOI: 10.1101/537175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of population structure in the design of RNA-based diagnostics for antibiotic resistance in Neisseria gonorrhoeae

Abstract: 21Quantitative assessment of antibiotic-responsive RNA transcripts holds promise for a 22 pump alleles acquired from commensal Neisseria, three resistant isolates with the C2611T 23s 126 rRNA mutation, and one resistant isolate with the A2059G 23s rRNA mutation (17, 18). A total 127 of ~258 million 50 bp paired-end reads were generated across 90 libraries. Each library had on 128 average 3.17 ± 0.16 million reads, and an average of 1.82 ± 0.11 million reads per library 129 mapped to the FA1090 (AE004969.1) ref… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The transcriptional profiles of the CRO RS isolates were similar to one another but 126 distinct from GCGS0457 (Supplementary Figure 2), with 1337 and 1410 annotated ORFs 127 significantly altered in abundance, respectively. The transcriptomic differences we observe may 128 partly reflect the genetic distance between these isolates 16 , as the resistant strains GCGS1095 129 and GCGS1014 are more closely related to one another than they are to GCGS0457. We 130 therefore compared GCGS0457 to its isogenic CRO RS transformants GCGS0457 RpoB R201H and 131 GCGS0457 RpoD E98K .…”
Section: Results and Discussion 34mentioning
confidence: 86%
“…The transcriptional profiles of the CRO RS isolates were similar to one another but 126 distinct from GCGS0457 (Supplementary Figure 2), with 1337 and 1410 annotated ORFs 127 significantly altered in abundance, respectively. The transcriptomic differences we observe may 128 partly reflect the genetic distance between these isolates 16 , as the resistant strains GCGS1095 129 and GCGS1014 are more closely related to one another than they are to GCGS0457. We 130 therefore compared GCGS0457 to its isogenic CRO RS transformants GCGS0457 RpoB R201H and 131 GCGS0457 RpoD E98K .…”
Section: Results and Discussion 34mentioning
confidence: 86%
“…Our analysis shows that expression levels of antibiotic target genes are significantly higher in susceptible isolates compared to nonsusceptible isolates. A recent RNA-based study identified candidate markers from the transcriptomes which were highly expressed in the susceptible isolates only [51].…”
Section: Discussionmentioning
confidence: 99%
“…A range of molecular diagnostic approaches have been evaluated, each with its strengths and limitations [42,[47][48][49][50][51]. While most methods target specific mutations to infer resistance, our approach targets the gene and its expression levels to infer resistance.…”
Section: Introductionmentioning
confidence: 99%